REDESIGN GOLEK BIS APPLICATION USING UCD (USER CENTERED DESIGN) APPROACH - Prasetya, Dhika Adi Prasetya; Purwati, Yuli; Suliswaningsih, Suliswaningsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: In the current digital era, transportation booking applications have become an integral part of people's daily lives. One of the preferred applications is the Suroboyo Bus Booking Application (GOBIS). GOBIS is a platform dedicated specifically to accessing Suroboyo Bus transportation services. However, with the advancement of technology and changing user needs, the GOBIS application also needs to be adjusted to remain relevant and meet expectations. Many users have complained about the application's ambiguous interface, unclear colors, and other issues. Therefore, a redesign of this application is necessary. This study employs the User-Centered Design (UCD) method and SUS testing to obtain a new design that can be implemented. The results show a significant improvement in application usability, with the average SUS score from users after the redesign process reaching 82.25, rated as